Le gouvernement du Québec et les milieux financiers de 1867 à 1920 - Vallières, Marc (L'Actualité économique, 1983)
AbstractThe author examines critically the financial needs of the Quebec Government between Confederation and the 1920s. He examines the negotiations between the government and the financial syndicates over the long term financial needs of the government. The impact of the short term financial needs of the government on its medium and long term financing is analyzed. The unique and powerful position of the Bank of Montreal is explained.